Pre-treatment Loss to Follow-up in Patients with Confirmed Pulmonary Tuberculosis in Niamey, Niger - Madougou, Assiatou Gagara Issoufou; Souleymane, Mahamadou Bassirou; Soumana, Alphazazi; Moussa, Souleymane Halidou (European Scientific Journal, ESJ, 2024)
Aims and Scope: Pre-treatment loss to follow-up (PTLFU) represents a major problem that hinders the management of tuberculosis. This paper focuses on determining the prevalence of lost to follow-up patients diagnosed with smear-positive pulmonary tuberculosis (SPPT) who are referred to other TB screening and treatment centers (TBSTC). Methods: This was a prospective, descriptive, and analytical study conducted over a six-month period between March and August 2019, in patients diagnosed with smear-positive pulmonary tuberculosis at NCFATRD and referred to Niamey and Tillaberi centers. A chi-square test was used with a significance level of P â‰¤ 0.05. Findings: 743 patients were diagnosed with SPPT, and 346 were referred to the TBSTC located in Niamey and Tillaberi cities. The prevalence of loss to follow-up before treatment in both Niamey and Tillaberi cities was 14.45% (50/343). Males represented 82% (41) of the cases with a sex ratio of 4.55. The mean age of the patients was 41.04 years. Patients not attending school, as well as those with primary school education, represented the majority of cases, accounting for 30% each. The majority of PTLFU (95.66%) were new cases of TB. Nearly half (42%) of PTLFU had traveled a distance of 6 to 15 km to receive TB screening. During the phone call follow up, only 12 patients (24%) were reached, of whom 7 (14%) were deceased. Conclusion: The prevalence of PTLFU remains high. Therefore, reinforcing the research of lost to follow-up patients is necessary to enhance tuberculosis control and management.